2001
DOI: 10.1203/00006450-200103000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Anion Generation in Human Milk Macrophages: Opsonin-Dependent Versus Opsonin-Independent Stimulation Compared with Blood Monocytes

Abstract: Macrophages are believed to play an important role within the immunoprotective effects of human breast milk. It was the purpose of this study to evaluate the capability of human milk macrophages (MM⌽) to generate superoxide anions (O 2 -) in comparison with peripheral blood monocytes (BMo) after stimulation with opsonized and unopsonized zymosan. Potential inhibitors of attachment and phagocytosis such as mannose and cytochalasin B were used. Expression of the mannose receptor on MM⌽ was demonstrated by staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…As the rst line of defence against invaders, neutrophils and monocytes generate huge amounts of superoxide anion, as reported by Anderson and Siwicki 20 . A number of different sh species have shown that beta-glucan actually increases superoxide anion generation by macrophages, which is contrary to the current study [29][30][31] . Nevertheless, the experimental designs used in each of these studies were distinctive in form of betaglucan, dosage, and administration time.…”
Section: Discussioncontrasting
confidence: 99%
“…As the rst line of defence against invaders, neutrophils and monocytes generate huge amounts of superoxide anion, as reported by Anderson and Siwicki 20 . A number of different sh species have shown that beta-glucan actually increases superoxide anion generation by macrophages, which is contrary to the current study [29][30][31] . Nevertheless, the experimental designs used in each of these studies were distinctive in form of betaglucan, dosage, and administration time.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, serum-free conditions fail to provide sources of either LPS-binding protein or opsonin. Results of in vitro studies 6,14 performed with cells from other species have indicated that the presence of LPS-binding protein and opsonin markedly increase the sensitivity of the cells to endotoxin and zymosan, thereby reflecting one of the roles of these proteins in vivo. We are unaware of any studies regarding expression of tissue factor by canine monocytes.…”
Section: Lpsmentioning
confidence: 99%
“…Procoagulant activity was determined by assessing the ability of cellular lysates to shorten the recalcification time of pooled equine plasma in a 1-stage clotting time assay. 14 Clotting times were determined in triplicate photoelectronically. c Procoagulant activities of samples were determined by reference to a standard curve generated by known dilutions (0.09% to 100%) of equine brain thromboplastin prepared in our laboratory.…”
Section: Animals and Isolation Of Mononuclear Cells-eighteenmentioning
confidence: 99%
“…Chemokinetic agents such as TNFα in human milk may aid in recruiting macrophages to mucosal sites of the recipient's alimentary tract [63]. The human milk macrophage appears lipid laden and has diminished respiratory burst patterns compared with blood monocytes after opsonized phagocytosis; however, when stimulated by opsonin-independent mechanisms, milk macrophages have greater respiratory burst than blood monocytes [147][148][149][150]. It is postulated that as the intestinal environment of the neonate offers only a small amount of opsonins (complement and immunoglobulin G [IgG]), such differentiation of lectinophagocytic properties of milk macrophages could render a greater advantage to the neonate [147].…”
Section: The Cellular Compartment Of Human Milk: Its Physiologic Relementioning
confidence: 99%
“…These macrophages survive in the neonatal gut environment during at least the first postnatal week and appear ideally suited to secrete various growth factors and cytokines to the recipient newborn gut. As a source of growth factors, macrophages that are present in human milk may "prime" the gut for continued epithelial maturation and closure [31, 41,44,61,81,147,150,[152][153][154][155]. Cell-to-cell interactions appear to play an integral part in the maturation of the GI tract of newborns [156].…”
Section: The Cellular Compartment Of Human Milk: Its Physiologic Relementioning
confidence: 99%